Sensitivity of imidazolinone-resistant red rice (Oryza sativa L.) to glyphosate and glufosinate - Cassol,Guilherme Vestena (2015)
Dose-response experiments were carried out to evaluate the sensitivity of imidazolinone-resistant red rice to nonselective herbicides currently used in rice-soybean rotation in Rio Grande do Sul. Two red rice biotypes previously identified as resistant and susceptible to the imidazolinone herbicides were treated with imazapic plus imazapic, glyphosate and glufosinate under nine herbicide rates. A non-linear log-logistic analysis was used to estimate the herbicide rate that provided 50% red rice control and dry weight reduction (GR50). Imidazolinone-resistant red rice exhibited greater GR50 values than imidazolinone-susceptible biotype for imazapyr plus imazapic. In contrast, both imidazolinone-resistant and susceptible red rice showed similar GR50values for glyphosate and glufosinate. These results indicate that glyphosate and glufosinate effectively control imidazolinone-resistant red rice at similar herbicide rates used to control imidazolinone-susceptible; however, integrated weed management practices must be adopted in rice-soybean rotation to delay resistance evolution of red rice populations to glyphosate and glufosinate